PENGANGKATAN ANAK ANGKAT MENURUT HUKUM - Hasan Syazali; T. Sabirin (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2022)
This study aims to determine the practice of adopting children as well as review Islamic law and positive law regarding child adoption in society. This study uses the method of